A modified QuEChERS method development to analyze tylosin and metronidazole antibiotics residue in shrimp (Penaeus monodon) using LC-ESI MS/MS - Islam, Sk Farzana; Kabir, Md. Humayun; Yasmin, Sabina; Alam, Mohammad Jahangir; Ahmed, Shamim; Rahman, Mohammad Shamsur (Frontiers in Sustainable Food Systems, 2023)
A modified QuEChERS method was developed for the simultaneous analysis of tylosin (Tyl) and metronidazole (MNZ) residues in shrimp samples using LC-ESI-MS/MS. The sample extraction procedure was based on modified QuEChERS, and the cleanup method was dispersive solid-phase extraction (dSPE). Octadecyl (C18) and primary secondary amine (PSA) sorbents were used in the dSPE cleanup. Analyte chromatographic separations were carried out using a ZORBAX RRHD Eclipse Plus C18 (100 × 2.1 mm, particle size 1.8 μm) column. The mobile phase consisted of dilluting 0.1% of formic acid with water and acetonitrile. The analyte was identified with multiple reaction monitoring and positive electrospray ionization. The analyte showed good linearity in the range of 0.5–50 μg/L for both analytes, and correlation coefficients (R2) were 0.9997 and 0.9998 for Tyl and MNZ, respectively. For the recovery study, three different concentration levels were spiked in triplicate. The recovery obtained a good result in the range of 81–85 % for Tyl with relative standard deviation (RSD) ≤ ± 4.9% and in the range of 85–88% for MNZ with RSD ≤ ± 4.07 %. The limit of detection (LOD) was estimated at 0.4 μg/kg for Tyl and 0.3 μg/kg for MNZ, and the limit of quantification (LOQ) was estimated at 1 μg/kg for Tyl and 0.9 μg/kg for MNZ. The linearity and recovery study showed that the method is validated and can be used to determine the Tyl and MNZ residues in shrimp. Finally, the method was applied to 25 real samples, which were collected from local markets and super shops in Dhaka and Khulna districts of Bangladesh, and only traces of Tyl were detected in one sample. This method is suitable for the regular analysis of Tyl and MNZ antibiotic residues in shrimp samples and can be used to ensure food safety in Bangladesh.